Phi, Fat, and the Mathematics of a Beautiful Midface. Issue 5 (September 2018) - Stein, Ran; Holds, John B.; Wulc, Allan E.; Swift, Arthur; Hartstein, Morris E.
Abstract : Purpose: The Golden ratio, or Phi, has been used to explain the substrates of two-dimensional beauty utilizing the faces of models. A "Phi point" has been identified at the apex of the cheek mound that can be targeted in filler injections. The authors report herein how they have applied this algorithm for surgical shaping of the "beautiful" cheek as a routine part of their lower blepharoplasty procedure. The authors present their technique and results with patients undergoing lower blepharoplasty along with the adjunct of liposculpture to areas of volume deficiency in the midface with a particular goal of enhancing the Phi point. Methods: This study was retrospective, consecutive, nonrandomized, interventional case series. The authors reviewed the medical records of 113 consecutive patients who underwent lower blepharoplasty with autologous fat transfer to the Phi point. The aesthetic outcome, patient satisfaction, and complication/revisions were evaluated. Results: One hundred two out of 113 patients achieved excellent lower lid position and cheek enhancement as assessed by both patient and surgeon. In these 102 patients, there was significant improvement in lower lid appearance, contour, transition to the cheek, and cheek projection as observed by the surgeon. Three patients required revision to achieve sufficient volume. Eight patients were satisfied with the outcome, nevertheless, requested additional filler injection to optimize. Conclusions: Lower blepharoplasty combined with autologous fat transfer to reshape the Phi point is a safe and reliable technique and another step further in our quest for recreating the beautiful face. Abstract : The Golden ratio, or Phi, has been used to explain the substrates of beauty on faces of models. Using liposculpture, the authors targeted the "Phi point" at the apex of the cheek mound during lower blepharoplasty.